Seroprevalence of parechovirus A1, A3 and A4 antibodies in Yamagata, Japan, between 1976 and 2017. Issue 12 (10th December 2020) - Mizuta, Katsumi; Komabayashi, Kenichi; Aoki, Yoko; Itagaki, Tsutomu; Ikeda, Tatsuya
Abstract : Introduction. Although new parechovirus A (PeVA) types, including parechovirus A3 (PeVA3) and PeVA4, have been reported in this century, there have not yet been any seroepidemiological studies on PeVA over a period of several decades. Hypothesis/Gap Statement. The authors hypothesize that PeVA3 and PeVA4 emerged recently. Aims. The aim was to clarify changes in the seroprevalence of PeVA1, PeVA3 and PeVA4. Methodology. Neutralizing antibodies (NT Abs) were measured among residents in Yamagata, Japan in 1976, 1983, 1985, 1990, 1999 and 2017. Results. The total NT Ab-positive rate for PeVA1 was between 90.7 and 100 % for all years analysed, with that for PeVA3 increasing from 39.6 % in 1976 to 69.6 % in 2017, and that for PeVA4 decreasing from 93.9 % in 1976 to 49.1 % in 2017. The distribution of NT Ab titres for PeVA1, PeVA3 and PeVA4 among those aged less than 20 years old was as follows: those ≥1 : 32 for PeVA1 were between 68.0–89.2 % for all years analysed; those ≥1 : 32 for PeVA3 was 15.4 % in 1976, 44.3–54.9 % in 1983–1990 and 64.8–68.0 % in 1999–2017; and those ≥1 : 32 for PeVA4 were between 49.1–67.2 % in 1976–1990, 41.3 % in 1999 and 23.8 % in 2017. Conclusions. Our findings in this seroepidemiological study over four decades suggested that PeVA1 has been stably endemic, while PeVA3 appeared around 1970s and has spread since then as an emerging disease, and occasional PeVA4 infections were common in 1970s and 1980s but have been decreasing for several decades in our community.